Black Women Leading Education for Social Justice in the Region of Baixada Fluminense, Rio de Janeiro, Brazil - Malachias, Rosangela; Laudino, Laudilea Aparecida de Lourdes; Balbino, Teresa Cristina dos Santos (Frontiers in Education, 2020)
This paper displays the interface between Education and Communication fields for developing narratives that can identify leadership among women who daily live social inequalities and violence. These studies, debates and researches happen at AFRODIÁSPORAS Research Center about Black Women, Audiovisual Culture and Educommunication in Urban Peripheries - Rio de Janeiro State University (UERJ) - School of Education from Baixada Fluminense (FEBF), Duque de Caxias city, RJ, Brazil.